Deconstructing matula (taboo), a multi-stakeholder narrative about LGBTI - Netshandama, V.O.; Mavhandu-Mudzusi, A.H.; Matshideze, P. (South African Journal of Higher Education, 2017)
ABSTRACT This article reports on a multi-stakeholder narrative about the lesbian, gay, bisexual, transgender and intersex (LGBTI) community in Venda in relation to the concept matula (taboo).We used a narrative enquiry design and collected data at a South African rural university using individual, face-to-face interviews with 15 participants (heterosexual and LGBTI individuals), and two focus group discussions with participants from the university and the community. Five themes emerged following narrative analysis, namely: (1) a definition of culture and matula; (2) the construction of the concept of matula, (3) Christian values, interpretations and influence; (4) the tendency to sexualise identity and (5) the knowledge of people about the salient reality of many truths. As there is a tendency of denialism in rural communities, the stories told provide the evidence needed of the presence of LGBTI individuals. We suggest the initiation of culturally congruent LGBTI advocacy programmes in rural areas.